Control predictivo de Estados Finitos para un convertidor bidireccional con diodos de enclavamiento - Verne, Santiago Andres (2011)
This work presents a multilevel back to back converter topology based on the Diode Clamped Multilevel Inverter. This configuration allows the direct linking of two medium voltage power systems with different frequency without stepup transformers for complete power flow control with low current distortion. Converters control and DC bus voltage balance is performed using a Finite-States Model Predictive Control approach. The conversion system is analized for several working conditions such as different modulation indexes, power flows and even different modulation schemes on both converters. The results allow to conclude the feasability of the proposal for the solution of power transmission and motor drive implementations in the medium voltage range without the necessity of step-up transformers.